LOSS OF LEGAL CERTAINTY IN THE TAXATION SYSTEM FOR TRANSFER OF LAND AND BUILDING RIGHTS - Muchtar, Andhyka (Faculty of Law, Universitas Pekalongan, 2024)
This investigate inspected the esteem of lawful certainty within the handle of exchanging rights to arrive and buildings where the framework in tax collection that ought to use the self-assessment framework isn't actualized but or maybe the Official Assessment system. These issues happen greatly in a few locales within the handle of collecting charges on the exchange of arrive rights not based on the charge collection framework that applies in Indonesia, so that the inclination of fiscus to decide charges comes about in hurt to the community. From the comes about of the ponder it was found that the activities taken by the assess specialists by conducting overviews come about in charges not in understanding with the exchange esteem decided by the citizen, other than that these activities are considered as activities that cannot be advocated as a frame of great administration. The irregularity of the nearby government as a burdening party in collecting charges in terms of the charge collection framework that ought to utilize the Self-Assessment Framework turns into the Official Assessment System. Therefore, another supporting system is needed that can strengthen the validity of the Self-Assessment system, namely a concept of a mutual agreement system or called a tax deal system.